Lymphocytic choriomeningitis virus (LCMV) infection of macaques: a model for Lassa fever (2011)
ABSTRACT: Arenaviruses such as Lassa fever virus (LASV) and lymphocytic choriomeningitis virus (LCMV) are benign in their natural reservoir hosts, and can occasionally cause severe viral hemorrhagic fever (VHF) in non-human primates and in human beings. LCMV is considerably more benign for human beings than Lassa virus, however certain strains, like the LCMV-WE strain, can cause severe disease when the virus is delivered as a high-dose inoculum. Here we describe a rhesus macaque model for Lassa fever that employs a virulent strain of LCMV. Since LASV must be studied within Biosafety Level-4 (BSL-4) facilities, the LCMV-infected macaque model has the advantage that it can be used at BSL-3. LCMV-induced disease is rarely as severe as other VHF, but it is similar in cases where vascular leakage leads to lethal systemic failure. The LCMV- infected macaque has been valuable for describing the course of disease with differing viral strains, doses and routes of infection. By monitoring system-wide changes in physiology and gene expression in a controlled experimental setting, it is possible to identify events that are pathognomonic for developing VHF and potential treatment targets.